Investigation of Potential Loss of Injectivity and Formation Integrity Due to Pressure Cycling. (January 2016) - Cerasi, Pierre; Walle, Lars Erik
Abstract: Two tests were carried out on weak sandstone outcrop samples, in order to assess whether sequences of injection of a pore fluid and shut-in could have a destabilising effect on the borehole wall of the hollow cylinder specimen. The fluid injected was kerosene, at room temperature, from the borehole radially outwards, while maintaining confinement by inserting the specimen in a rubber sleeve, in a pressurized oil bath. Although no visible signs of any damage could be seen, cumulative deformation occurs at each injection cycle, with net effect of slight borehole enlargement. An analytic analysis suggested however that under the confining stress conditions of the tests, plastic deformation should cumulate in the opposite direction, with borehole diameter shrinkage. This is despite a very good match in terms of absolute deformation values. Further analyses should resolve the issue and allow one to predict whether cyclic injection may have an impact on permeability or formation integrity.